Alih Kode dan Campur Kode pada Novel Cinta Dalam Diam Karya Shineeminka - Endang Kusnawan; Masrin Masrin (Universitas Indraprasta PGRI, 2021)
This study aims to analyze the linguistic phenomena in the form of code switching and code mixing including the causal factors and functions attached to conversational events in the novel Cinta dalam Diam by Shineeminka. The data analyzed include: 1) Forms, events, functions, and factors that cause code switching in Shineeminka's novel Cinta Dalam Diam. 2) Forms, events, functions, and factors that cause code-mixing in Shineeminka's novel Cinta dalam Diam. The research method used to analyze this novel is a qualitative approach. Data collection techniques by reading, listening, taking notes and library techniques. The results of the analysis can be concluded as follows: 1) There are forms, events, functions, and factors that cause code switching in the novel Cinta dalam Diam by Shineeminka 2) There are forms, events, functions, and factors that cause code mixing in the novel Cinta dalam Diam by Shineeminka. This research is useful to improve the quality of Indonesian language learning, especially about language. Keywords: Code Switching, Code Mixing, Novel “Cinta dalam Diam”